Psychological disturbance in Ireland, in England and in Irish emigrants to England - comparative study - Cochrane, Raymond; Stopes-Roe, Mary (Economic & Social Studies, 1979)
A community survey involving 200 Irish emigrants to England, 200 natives of England and 200 residents of the Republic of Ireland was conducted to test a number of hypotheses drawn from mental hospital admission statistics. Contrary to the pattern revealed by these statistics, there was significantly less psychological disturbance amongst the immigrants than amongst the natives of England. It was also found that the Irish group had no more symptoms than the English. It is concluded that the high rate of mental hospital admissions among Irish immigrants is attributable to a small, separate group of deteriorated immigrants, rather than reflecting high levels of psychopathology throughout the community.
Keywords: Mental health - Irish emigrants; Emigration - Ireland